2023
DOI: 10.1021/acs.jchemed.3c00227
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App to Quantify pH Strips and Monitor Titrations: Smartphone-Aided Chemical Education and Classroom Demonstrations

Jiaxing Li,
Marissa L. O’Neill,
Connor Pattison
et al.

Abstract: pH determination and acid−base titrations are essential experiments performed by high school and university undergraduate students alike throughout their chemistry education. While these experiments often rely on conventional pH meters for quantification and pH test strips or indicators for qualitative assessments, we demonstrated herein that a smartphone-based pH determination technique, performing digital image analysis, particularly the determination of either the dominant wavelength or the RGB intensities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The idea of using smartphones, scanners, and digital cameras for scientific measurements and data acquisition is particularly intriguing to these students. It aligns with their everyday experiences and provides a tangible connection between their technological fluency and the world of analytical chemistry. …”
Section: Introductionmentioning
confidence: 81%
“…The idea of using smartphones, scanners, and digital cameras for scientific measurements and data acquisition is particularly intriguing to these students. It aligns with their everyday experiences and provides a tangible connection between their technological fluency and the world of analytical chemistry. …”
Section: Introductionmentioning
confidence: 81%
“…51 Spreadsheet App, contains the equivalence points determined using a pH meter and smartphone app. 52 Yadav et al 53 determined that the fluoride concentrations in real samples using a standard method…”
Section: Methodsmentioning
confidence: 99%
“…Comparing the results obtained using a pH meter and an app (spreadsheet App; supporting information). 52 The Shapiro-Wilk test showed that the data was normally distributed (p-value = 0.587).…”
Section: Comparing Two Dependent Groups (T-paired Test) 300mentioning
confidence: 99%
“…Titration aids in precise determination of unknown concentrations of identified analytes . In the laboratory, several types of titrations with different procedures and goals may be used. Acid–base titrations are commonly used volumetric analysis techniques in laboratories of secondary and postsecondary educational institutions. …”
Section: Introductionmentioning
confidence: 99%